SULTAN YILDIRIM BAYEZID AND OTTOMANS IN THE LETTERS OF MANUEL II PALAEOLOGUS - Murat KEÇİŞ (Fırat University, 2019)
The letters of the Byzantine emperor Manuel II Palaeologos, studied and exploited by Byzantinists since they were published for the first time by E. Legrand in 1893, are available in a new edition by G. Dennis, in which they are translated into English, accompanied by the appropriate comments. These letters constitute a most valuable contemporary source for the years 1382–1417 because they help to fill one part of the much deplored gap in Byzantine historiography. Moreover, they include evidence which sheds light on some details of early Ottoman history, as will appear from the following analysis of Manuel’s material dealing with the conflict between the sultan Bayezid I and the ruler of Sivas, ?adi Burhan al-Din A?mad in 1391. Manuel II attended in the military campaigns of 1391 as a vassal of the Ottoman sultan and while Ottoman headquarter, he wrote eight letters to various eminent personages as originally being Venetian citizen Demetrios Kydones, Kabasilas, Phothos, Konstantin Asanes in the Byzantine Palace. These letters of Emperor Manuel has been thought to write in order to inform both the people of Constantinopolis and the Venetians who are willing to learn the fate of the Byzantine emperor at that time, the development of campaign. These letters, which are Dennis edition under numbers 8-21, contain information about the progress of the campaign which can be considered relatively reliable and impartial. In this article, dicussing the reliability of letters as a historical source, studied to show the importance of Ottoman history and are presented by interesting samples the relations of between Sultan Bayezid I and Byzantine Emperor Manuel II Palaeologus.